2015
DOI: 10.3144/expresspolymlett.2015.40
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanoplatelets-reinforced polyetherimide foams prepared by water vapor-induced phase separation

Abstract: Abstract. The present work considers the preparation of medium-density polyetherimide foams reinforced with variable amounts of graphene nanoplatelets (1-10 wt%) by means of water vapor-induced phase separation (WVIPS) and their characterization . A homogeneous closed-cell structure with cell sizes around 10 µm was obtained, with foams exhibiting zero crystallinity according to X-ray diffraction (XRD). Thermogravimetric analysis under nitrogen showed a two-step thermal decomposition behaviour for both unfilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…Figure shows the thermogravimetric weight loss and respective first derivative (dTG) thermograms of pure PEI foam and Series 2 foams. PEI‐GnP foams presented a characteristic two‐step thermal decomposition similar to pure PEI foam at around 530°C and 580°C, respectively related to the rupture of the aliphatic part of PEI followed by a second stage of decomposition of the aromatic part . The residual weight remained above 50 wt% at 1,000°C for all foams.…”
Section: Resultsmentioning
confidence: 87%
“…Figure shows the thermogravimetric weight loss and respective first derivative (dTG) thermograms of pure PEI foam and Series 2 foams. PEI‐GnP foams presented a characteristic two‐step thermal decomposition similar to pure PEI foam at around 530°C and 580°C, respectively related to the rupture of the aliphatic part of PEI followed by a second stage of decomposition of the aromatic part . The residual weight remained above 50 wt% at 1,000°C for all foams.…”
Section: Resultsmentioning
confidence: 87%
“…Previously grinded PAI was firstly dissolved in NMP (12.5 g of PAI/50 g of NMP solution, i.e., a 20 wt% PAI solution) at 75°C and kept stirring at 450 rpm for 24 h using a MBG05E OVAN magnetic stirrer. Afterward, grinded PEI was added into parts of the former dissolution in order to obtain solutions having different proportions of PEI/PAI (0, 50 and 75 wt% PEI referred to PAI) and kept at the same temperature and stirring conditions till complete dissolution for approximately 24 h. This polymer solution was poured on a flat glass and exposed to air with a controlled humidity of 75% at room temperature for 7 days, which promoted foaming by WVIPS, as discussed in a previous paper [11]. Water absorption was accelerated by placing the already semi-solid foams in cold water.…”
Section: Foam Preparationmentioning
confidence: 99%
“…In this method, a proper solvent is first chosen in order to obtain a homogeneous solution, which finally results in a cellular structure due to the nucleation of cells associated with the occurrence of phase separation promoted by the induction of water vapor from the humid atmosphere. Additionally, the addition of nanofillers such as graphene [10,11], graphene/Fe 3 O 4 [12] or nickel nanoparticles [13], has been shown to lead to foams prepared using this method with multifunctional properties.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…reported a kind of PEI/GN composite foam for electromagnetic interference shielding and found that electromagnetic interference shielding increased from 17 to 44 dB g –1 cm 3 , and a tensile strength as high as ca 8 MPa was achieved. Abbasi et al . prepared PEI/GN foam through the method of water‐vapor‐induced phase separation (WVIPS) and observed that all foams presented a homogeneous cellular morphology.…”
Section: Introductionmentioning
confidence: 99%